Managing food safety and hygiene : governance and regulation as risk management - Hutter, Bridget M.; Jones, Clive (Edward Elgar, 2011)
Bridget Hutter considers the understandings of risk and regulation held by those in business and considers the compliance pressures on managers and owners, and how these relate to understandings of risk and uncertainty